The epigenetic reader Brd4 is required for osteoblast differentiation. Issue 6 (23rd December 2019) - Paradise, Christopher R.; Galvan, M. Lizeth; Kubrova, Eva; Bowden, Sierra; Liu, Esther; Carstens, Mason F.; Thaler, Roman; Stein, Gary S.; van Wijnen, Andre J.; Dudakovic, Amel
Abstract: Transcription networks and epigenetic mechanisms including DNA methylation, histone modifications, and noncoding RNAs control lineage commitment of multipotent mesenchymal progenitor cells. Proteins that read, write, and erase histone tail modifications curate and interpret the highly intricate histone code. Epigenetic reader proteins that recognize and bind histone marks provide a crucial link between histone modifications and their downstream biological effects. Here, we investigate the role of bromodomain‐containing (BRD) proteins, which recognize acetylated histones, during osteogenic differentiation. Using RNA‐sequencing (RNA‐seq) analysis, we screened for BRD proteins ( n = 40) that are robustly expressed in MC3T3 osteoblasts. We focused functional follow‐up studies on Brd2 and Brd4 which are highly expressed in MC3T3 preosteoblasts and represent "bromodomain and extra terminal domain" (BET) proteins that are sensitive to pharmacological agents (BET inhibitors). We show that small interfering RNA depletion of Brd4 has stronger inhibitory effects on osteoblast differentiation than Brd2 loss as measured by osteoblast‐related gene expression, extracellular matrix deposition, and alkaline phosphatase activity. Similar effects on osteoblast differentiation are seen with the BET inhibitor +JQ1, and this effect is reversible upon its removal indicating that this small molecule has no lasting effects on the differentiation capacity of MC3T3 cells. Mechanistically, we find that Brd4 binds at known Runx2 binding sites in promoters of bone‐related genes. Collectively, these findings suggest that Brd4 is recruited to osteoblast‐specific genes and may cooperate with bone‐related transcription factors to promote osteoblast lineage commitment and maturation. Abstract : This study demonstrates that acetylated histone reader Brd4 is highly expressed in MC3T3 preosteoblasts and its function is required for osteogenic differentiation. Mechanistically, Brd4 is recruited to osteoblast‐specific genes and may cooperate with bone‐related transcription factors (e.g., Runx2) to promote osteoblast differentiation.